2007
DOI: 10.1086/522184
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Negative Prosthetic Joint Infection

Abstract: Background. Culture-negative (CN) prosthetic joint infection (PJI) has not been well studied. We performed a retrospective cohort study to define the demographic characteristics and determine the outcome of patients with CN PJI.Methods. All cases of CN total hip arthroplasty and total knee arthroplasty infections (using a strict case definition) treated at our institution from January 1990 through December 1999 were analyzed. Kaplan-Meier survival methods were used to determine the cumulative probability of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
280
2
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(317 citation statements)
references
References 23 publications
14
280
2
10
Order By: Relevance
“…However, the available tests for diagnosis of PJI are far from perfect. Cultures, for example, are negative in 7% to 12% of patients with PJI [5,10,16,19]. Culture-negative PJI can potentially complicate case classification and management and is an additional source of stress for both the patient and surgeon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the available tests for diagnosis of PJI are far from perfect. Cultures, for example, are negative in 7% to 12% of patients with PJI [5,10,16,19]. Culture-negative PJI can potentially complicate case classification and management and is an additional source of stress for both the patient and surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…Culture-negative PJI can potentially complicate case classification and management and is an additional source of stress for both the patient and surgeon. Antimicrobial treatments have been reported to be a cause of culture-negative PJI [5,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…contamination of samples may result in false-positive results [6]. Some authors have suggested different adjunctive criteria [5,27,36,38] to overcome shortcomings of bacteriologic culture, leading to discrepancy in their inclusion and exclusion criteria.…”
Section: Introductionmentioning
confidence: 99%
“…The technique is based on the amplification of bacterial 16S ribosomal DNA [6]. Criteria for definite PJI included the presence of a sinus tract communicating with the prosthesis or purulence surrounding the prosthesis at the time of surgery or acute or chronic inflammation consistent with infection on histopathologic examination [1,7]. Infection was excluded when the above-mentioned criteria were not fulfilled, no antimicrobial treatment was administered after the episode, and no relapse occurred for at least 1 year.…”
mentioning
confidence: 99%